Protectionism and compliance with the GATT article XXIV in selected regional trade arrangements - Grimett, Leticia Anthea (Rhodes University, Faculty of Law, Law, 1999)
The General Agreement on Tariffs and Trade (GATT) 1994 has resulted in the GATT Contracting States making a renewed commitment to freer global trade and trade liberalisation. These Contracting States signalled their commitment to GATT policies and principles by undertaking to abolish all those non-tariff barriers which were not converted to tariffs and to decrease all tariffs applied by their domestic economies. The movement away from protectionism is intended to bring contracting states in line with the GATT most-favoured-nation and national treatment principles. The only exceptions to these principles are the regional trade arrangements which can be implemented in accordance with Article XXIV of GATT 1947 and the Understanding on the Implementation of Article XXIV of GATT 1947. Regional trade arrangements such as customs unions and free-trade areas have been allowed by the GATT as they are deemed to promote trade liberalisation through the removal of substantially all trade restrictions between countries party to these trade arrangements. In practice this has not been the case, however, as these regional trade arrangements have been known to apply very protectionist trade policies. This research determines whether regional trade arrangements are inherently protective ie does the nature of these regional trade arrangements encourage protectionism? The external trade policies of the European Union (EU), Association of Southeast Asian Nations (ASEAN), Southern African Development Community (SADC) and the Southern African Customs Union (SACU) are analysed to determine whether the contracting parties to regional trade arrangements have corrupted the GATT provisions and so contributed towards the protectionist nature of these regional trade arrangements. The internal trade provisions relating to the implementation of these regional trade arrangements have also been discussed to determine their compliance with Article XXIV of GATT 1947. As all the selected regional trade arrangements have direct or indirect links to South Africa, the implications of the policies chosen by these parties for South Africa have also been discussed. Analysis of the EU, SADC, SACU and ASEAN has shown that prior to the adoption of the GATT 1994, the free-trade areas and customs unions were not implemented in accordance with Article XXIV provisions. These regional trade arrangements have been moulded to fit the economic aspirations of the relevant contracting states. Of the regional trade arrangements accepted by the GATT, free-trade areas have been found to be the least protectionist and are the least likely to be perverted by contracting parties. Customs unions, on the other hand, may encourage contracting parties to protect their economies as they rely on group participation rather than individual participation. Individual Member States become responsible to the group which provides these states with greater economic power. As a result Member States are motivated to protect the new group entity from outside competition. In this way, they are inherently protective. Safeguards are therefore necessary to protect individual non-Member States from such behaviour. The implications of protectionism for South Africa, SADC and SACU have also been discussed.
Keywords: General Agreement on Tariffs and Trade (Organization); International trade; Tariff -- Law and legislation; Protectionism; Free trade -- South Africa; South Africa -- Commerce